Natural lung-tropic TH9 cells: a sharp weapon for established lung metastases - Tao Chen; Hao Zhou; Shuming Li; Nong Lin; Yixuan Feng; Zhijian Cai; Chenxiao Qiao; Eloy Yinwang; Shengdong Wang; Xuehuan Wen; Xiangang Jin; Yucheng Xue; et al. (Journal for ImmunoTherapy of Cancer)
Background Lung metastasis remains the primary cause of tumor-related mortality, with limited treatment options and unsatisfactory efficacy. In preclinical studies, T helper 9 (TH9) cells have shown promise in treating solid tumors. However, it is unclear whether TH9 cells can tackle more challenging situations, such as established lung metastases. Moreover, comprehensive exploration into the nuanced biological attributes of TH9 cells is imperative to further unravel their therapeutic potential.Methods We adoptively transferred TH1, TH9, and TH17 cells into subcutaneous, in situ, and established lung metastases models of osteosarcoma and triple-negative breast cancer, respectively, comparing their therapeutic efficacy within each distinct model. We employed flow cytometry and an in vivo imaging system to evaluate the accumulation patterns of TH1, TH9, and TH17 cells in the lungs after transfusion. We conducted bulk RNA sequencing on in vitro differentiated TH9 cells to elucidate the chemokine receptor CXCR4, which governs their heightened pulmonary tropism relative to TH1 and TH17 cell counterparts. Using Cd4cre Cxcr4 flox/flox mice, we investigate the effects of CXCR4 on the lung tropism of TH9 cells. We performed mass spectrometry to identify the E3 ligase responsible for CXCR4 ubiquitination and elucidated the mechanism governing CXCR4 expression within TH9 cellular milieu. Ultimately, we analyzed the tumor immune composition after TH9 cell transfusion and evaluated the therapeutic efficacy of adjunctive anti-programmed cell death protein-1 (PD-1) therapy in conjunction with TH9 cells.Results In this study, we provide evidence that TH9 cells exhibit higher lung tropism than TH1 and TH17 cells, thereby exhibiting exceptional efficacy in combating established lung metastases. CXCR4-CXCL12 axis is responsible for lung tropism of TH9 cells as ablating CXCR4 in CD4+ T cells reverses their lung accumulation. Mechanistically, tumor necrosis factor receptor-associated factor 6 (TRAF6)-driven hyperactivation of NF-κB signaling in TH9 cells inhibited ITCH-mediated ubiquitination of CXCR4, resulting in increased CXCR4 accumulation and enhanced lung tropism of TH9 cells. Besides, TH9 cells’ transfusion significantly improved the immunosuppressed microenvironment. TH9 cells and anti-PD-1 exhibit synergistic effects in tumor control.Conclusions Our findings emphasized the innate lung tropism of TH9 cells driven by the activation of TRAF6, which supports the potential of TH9 cells as a promising therapy for established lung metastases.